2019
DOI: 10.1007/s12178-019-09528-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondritis dissecans lesions of the capitellum in overhead athletes: a review of current evidence and proposed treatment algorithm

Abstract: Purpose of the Review To review the most recent literature on osteochondritis dissecans (OCD) lesions of the capitellum in overhead athletes and describe a treatment algorithm based on current best evidence and surgeon experience. Recent Findings Recent research has included larger cohort studies with longer follow-up as well as quality systematic reviews and meta-analyses. These studies have focused on understanding how lesion characteristics such as size, location, and appearance on advanced imaging can pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 79 publications
0
49
0
Order By: Relevance
“…This is in line with prior data suggesting that patients with open physes or those who are younger have better outcomes with operative and nonoperative management. 3,9,15,19,20 We observed significant improvements in ROM in flexion, extension, and arc of elbow motion in this cohort, without difference with respect to surgical technique or sporting activities. Prior authors have also demonstrated improvements in flexion and/or extension ROM.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 54%
See 1 more Smart Citation
“…This is in line with prior data suggesting that patients with open physes or those who are younger have better outcomes with operative and nonoperative management. 3,9,15,19,20 We observed significant improvements in ROM in flexion, extension, and arc of elbow motion in this cohort, without difference with respect to surgical technique or sporting activities. Prior authors have also demonstrated improvements in flexion and/or extension ROM.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 54%
“…This is in line with prior data suggesting that patients with open physes or those who are younger have better outcomes with operative and nonoperative management. 3,9,15,19,20…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis by Logli et al. 8 showed that among 444 patients, there was only 1 knee donor site–related complication, which was a superficial wound infection.…”
Section: Discussionmentioning
confidence: 99%
“…Donor-site morbidity is a concern, so the senior surgeon often backfills harvest sites with allograft in competitive athletes. However, a meta-analysis by Logli et al 8 showed that among 444 patients, there was only 1 knee donor siteerelated complication, which was a superficial wound infection.…”
Section: Pitfallsmentioning
confidence: 99%
“…Several surgical options are available for the treatment of COCDs, including debridement, microfracture, fragment fixation, and autologous osteochondral grafting (OG). 14 Cohort studies have suggested that single-plug OG can be used to achieve good pain relief and improved functional outcomes. 2,19,26,28 Additionally, use of OG in other joints has been shown to lead to superior outcomes as compared with use of microfracture and debridement.…”
mentioning
confidence: 99%